2006
DOI: 10.1073/pnas.0503776103
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous shedding ofEscherichia coliO157 in cattle and its implications for control

Abstract: Identification of the relative importance of within-and betweenhost variability in infectiousness and the impact of these heterogeneities on the transmission dynamics of infectious agents can enable efficient targeting of control measures. Cattle, a major reservoir host for the zoonotic pathogen Escherichia coli O157, are known to exhibit a high degree of heterogeneity in bacterial shedding densities. By relating bacterial count to infectiousness and fitting dynamic epidemiological models to prevalence data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
233
7
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(252 citation statements)
references
References 55 publications
11
233
7
1
Order By: Relevance
“…Because no preharvest intervention could be 100% effective (22,29), a few animals may be excreting high numbers of E. coli O157:H7 during transport and lairage. In the high-density environments of transport and lairage, a few animals shedding high numbers of E. coli O157: H7 could contaminate the hides of several animals in that lot (17,18). In the current study, a small number of the cattle shedding E. coli O157:H7 (8.6% in group 1) can lead to dramatic increases in hide prevalence and counts (from 28 to 89% and from 6 to 16 animals with high hide numbers) in a very short period (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Because no preharvest intervention could be 100% effective (22,29), a few animals may be excreting high numbers of E. coli O157:H7 during transport and lairage. In the high-density environments of transport and lairage, a few animals shedding high numbers of E. coli O157: H7 could contaminate the hides of several animals in that lot (17,18). In the current study, a small number of the cattle shedding E. coli O157:H7 (8.6% in group 1) can lead to dramatic increases in hide prevalence and counts (from 28 to 89% and from 6 to 16 animals with high hide numbers) in a very short period (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of transmission in animal hosts have also shown a scaling of transmission fitness with pathogen load, e.g. Salmonella and Clostridium difficile transmission in mice [61,62] and Escherichia coli in cattle [63]. All these examples suggest that for some diseases and under some scenarios, infectiousness might be directly determined by pathogen load.…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…Verocytotoxinproducing E. coli O157 is usually widespread in fecally contaminated environments of infected animals and tends to circulate between individual animals within close proximity of each other or indirectly via other epidemiological routes. 4 Currently, during outbreak investigations, a large number (often 100 to 200 or more) of fecal samples are examined for VTEC O157 based on a 95% confidence of detecting at least 1 positive at a minimum estimated within-group prevalence of 10% within each distinct epidemiological group. Adopting a pooled approach for sample collection from epidemiological groups is potentially much more practical, cost-effective, and safer for the sampler as it does not require handling of individual cattle, provided it offers adequate statistical confidence and test sensitivity.…”
Section: Introductionmentioning
confidence: 99%